Determination and removal of organochlorine pesticides by activated macadamia nutshell in water and sediment alongside Vaal River using GC-MS - Phele, Mokete John (Vaal University of Technology, 2017)
A rapid and reliable method was developed and applied for the simultaneous determination of 15 organochlorine pesticides (OCPs) in water and sediment. OCPs are continually detected in the environment due to their increasing applications in agriculture and industry, their presence in the environment are not desirable since they are well known to have negative impact in humans and animals. Thus, there has been a continual demand to monitor the presence of OCPs within the environment. The analytical technique employed was gas chromatography equipped mass spectrometer (GC–MS). The correlation coefficients from linear regression for the analysed concentrations were >0.9998. The limits of detection (LODs) varied between 0.068 ppm for 4, 4-DDT and 0.021 ppm for endrin, and the limits of quantitation (LOQs) ranged from 0.06 to 0.23 ppm. The average recoveries varied between 92.08 and 99.71 %. Relative standard deviations (RSD %) ranged from 2.01 to 6.42 %. Sediment samples were extracted using accelerated solvent extraction (ASE), it was found that the limits of quantification ranged from 0.002 to 0.004 ppm, and the average recoveries were in the range 63.2 % - 96 % with standard deviations in the range 3 %-12 %. Macadamia nutshell was characterised using FTIR, spectroscopy and scanning electron microscope (SEM). The functional groups present were found to be O-H stretching vibration of hydrogen bonded hydroxyl groups, aliphatic C-H stretching vibration and C-OH stretching of phenolic groups. SEM image revealed that the material consisted of flaky long fold-like structure which are typical of plant materials.
M. Tech. (Department of Chemistry, Faculty of Applied and Computer Sciences), Vaal University of Technology.
Keywords: Organochlorine pesticides (OCPs); Water; Sediment; Activated macadamia nutshell; Pesticides removal; Dissertations, Academics -- South Africa.; Pesticides--Environmental aspects.; Organochlorine compounds.; Regression analysis.